METHOD OF COMMUNICATIONS ISLAMIC EDUCATIONAL INSTITUTIONS IN BUILDING BRANDING IMAGE SYMBOLIC INTERACTION STUDIES - Ansori, Ansori; Hefniy, Hefniy; Baharun, Hasan; Agus, Abu Hasan; Zaini, Abdul Wahid (Managere: Indonesian Journal of Educational Management, 2023)
The focus of this study is to investigate the influence of integration between pesantren and universities in shaping student character, taking into account aspects such as values, culture, and habits reflected in campus life. The purpose of this study is to understand more deeply how this integration affects student character building, as well as to identify effective strategies in optimizing the positive influence of pesantren-university integration in the context of character education in universities. This study used a qualitative approach with interviews and observations of UNUJA students and academic staff. The results showed that the integration between pesantren and universities has a significant impact on the character formation of UNUJA students. The values, culture, and customs of pesantren are reflected in various aspects of campus life, and these influences shape the identity and personality of students. In addition, this study also identified several effective strategies in optimizing the positive influence of pesantren-university integration for character education in universities. Research has also identified effective strategies to increase the positive influence of such integration in character education in higher education. This shows that pesantren values have a significant positive impact on higher education, as well as strengthen the institution's commitment in developing noble morals and character.